If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5y + -4) + -1(5x + 11) = 0 Reorder the terms: (-4 + 3x + 5y) + -1(5x + 11) = 0 Remove parenthesis around (-4 + 3x + 5y) -4 + 3x + 5y + -1(5x + 11) = 0 Reorder the terms: -4 + 3x + 5y + -1(11 + 5x) = 0 -4 + 3x + 5y + (11 * -1 + 5x * -1) = 0 -4 + 3x + 5y + (-11 + -5x) = 0 Reorder the terms: -4 + -11 + 3x + -5x + 5y = 0 Combine like terms: -4 + -11 = -15 -15 + 3x + -5x + 5y = 0 Combine like terms: 3x + -5x = -2x -15 + -2x + 5y = 0 Solving -15 + -2x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + -2x + 15 + 5y = 0 + 15 Reorder the terms: -15 + 15 + -2x + 5y = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -2x + 5y = 0 + 15 -2x + 5y = 0 + 15 Combine like terms: 0 + 15 = 15 -2x + 5y = 15 Add '-5y' to each side of the equation. -2x + 5y + -5y = 15 + -5y Combine like terms: 5y + -5y = 0 -2x + 0 = 15 + -5y -2x = 15 + -5y Divide each side by '-2'. x = -7.5 + 2.5y Simplifying x = -7.5 + 2.5y
| sec*x-secx=2 | | 7r-3=2r-7 | | 0=-16t^2+40t-4 | | 9+3(2u-3)=-3(6u-6)+8u | | (x+8)(x+6)=32 | | 8(9b+4)=-32 | | 2-(2c+3)=-3(3c-4) | | 2/3b9 | | (3x+5)(9x-5)=0 | | 2x^2+3x-2x-3=18 | | 11.5(4+X)= | | 5z+5=6-4z+17 | | 6=a+9 | | sec*x-secx-2=0 | | 2(2y+1)=(5y-2) | | 5x+9+4x=9+8+(-7) | | log(9x^3)=2 | | 7a^2-5a-5=-5 | | X^2-25=10 | | 2(25-5)=2(26+5) | | 5x+9+4x=9+8 | | 21/3×5-11 | | 2/7=x/7 | | (X^-3y^3)^-4/(y^3x^-5)^-5 | | 8x^(13/3)-24=0 | | 2*cosx=2*cos*2x | | 12z-4x=-7 | | 10h-10=10-10h | | x^9/2 | | 38x+66=180 | | 3x-(5x)= | | 2n-4=5n+5 |